THEOLOGICAL AND SCIENTIFIC METAPHORS. A PHILOSOPHICAL CRITIQUE: THE DIFFICULTIES OF A DIALOGUE BASED ON METAPHORS - Marcel BODEA (Studia Universitatis Babeș-Bolyai. Philosophia)
The specific languages referred to in this presentation are: philosophical language, scientific language, theological language and mathematical language. The specific metaphors referred to in this presentation are: metaphors of physics, metaphors of theology and metaphors of mathematics. Both theological and scientific languages have metaphorical components but, the activity of interpretation of metaphors in science and in theology does not have an interdisciplinary character. Of course, we cannot speak about dialogue without communication between various fields, without passing from one specialized language to another specialized language. In the extremely delicate but possible dialogue between science and theology, first must be seen the “strong differences” between which can hardly be built bridges for dialogue. Not least, and perhaps equally important, must also be seen the “quicksand” of the languages, as metaphors are, over which building bridges for dialogue can lead to communication but it can lead as well to misunderstanding and confusion. The question raised in this paper is: Is it possible to be initiated a dialogue between science and theology starting from metaphors of these languages? The present paper proposes to suggest this aspect.